Strategic effects and the Porter hypothesis - André, Francisco J. (Munich, 2015)
"Environmental protection and firms' competitiveness are typically seen as conflicting elements as firms tend to ignore the environmental consequences of their actions and any regulation forcing them to modify their policies can only make them worse-off. Contrarily to this traditional paradigm, the Porter Hypothesis suggests the existence of "low hanging fruits" in the sense that some environmental policies may simultaneously benefit the environment and domestic competitiveness. Our aim is to identify the main theoretical arguments that have been proposed in the literature to support the validity of the Porter Hypothesis and pick the most significant contributions paying special attention to the strategic and international trade aspects. After presenting some general issues and different interpretations of the Porter Hypothesis, we review different theoretical explanations such as the generation of scarcity rents, the use of environmental regulation by national governments as an instrument of strategic trade policy, the existence of externalities in technology adoption, the interaction with output quality competition and the existence of information incompleteness."